(untitled) (Altre Modernità, 2012)
Assuming that translation is necessary in all specialized languages for either informative or even persuasive purposes as well as for popularizing objectives, this contribution considers the translation needs of two types of specialized languages, legal English and English for business and management. Their requirements, strictly connected with their specific discourse communities, are analysed from the point of view of a linguist involved in an interdisciplinary scientific group, which represents a particular situation in non-literary, non-linguistic faculties. In this context, the jurists’ needs seem to be more concerned with definitory, terminological issues, whereas in business the distribution of information and textual organization prevail. Evidence is given that, in the two sectors taken into consideration, activities such as translation and re-writing apply different strategies at a pragmatic and textual level, also in view of possible intercultural implications.